2014
DOI: 10.1515/bmt-2013-0121
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in anthropometric parameters between different models affect intervertebral rotations when loading finite element models with muscle forces from inverse static analyses

Abstract: In only a few published finite element (FE) simulations have muscle forces been applied to the spine. Recently, muscle forces determined using an inverse static (IS) model of the spine were transferred to a spinal FE model, and the effect of methodical parameters was investigated. However, the sensitivity of anthropometric differences between FE and IS models, such as body height and spinal orientation, was not considered. The aim of this sensitivity study was to determine the influence of those differences on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…However, it was difficult to share the above-mentioned muscle forces for other researchers due to their private optimization techniques. We have previously carried out sensitivity studies when transferring muscle forces from a shared inverse static model to load an FE model [ 16 , 17 ]. The findings showed that many parameters have to be considered when combining two biomechanical models and artificial errors may be induced in the model which may have a significant impact on the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was difficult to share the above-mentioned muscle forces for other researchers due to their private optimization techniques. We have previously carried out sensitivity studies when transferring muscle forces from a shared inverse static model to load an FE model [ 16 , 17 ]. The findings showed that many parameters have to be considered when combining two biomechanical models and artificial errors may be induced in the model which may have a significant impact on the outcome.…”
Section: Introductionmentioning
confidence: 99%